TEACHERS’ PROBLEMS AND SOLUTIONS IN ASSESSING STUDENTS’ WRITING IN SENIOR HIGH SCHOOL LEVEL: AUTHENTIC ASSESSMENT OR TRADITIONAL ASSESSMENT - RONAULI SIHOMBING (Sriwijaya University Learning and Education International Conference, 2016)
English is one of the core subjects at junior and senior high school in Indonesia. Writingas the productive skill of learning English claims that the teachers have to involve indesigning the writing task or assignment and designing or adapting the scoring rubric.Assessing students’ writing is nota simple task. The following research studies aboutthe teachers’ problems in assessing students’ writing at the senior high school level. Theresearch was conducted for the reason to investigate a further information aboutteachers’ problemsand explore the solutions in assessing the students’ writing. Theresearch was undertaken at a well-known public senior high school in West Java,Indonesia. This research employs a qualitative research. A semi structured interviewwas used to collect the data by interviewing the English teachers in the school. The datain the form of extended text were analyzed and interpreted to get the final results.Assessing writing is a complex task for teachers. It was found that there are someproblems faced by the teachers in assessing students’ writing. One of which is thatteachers doesn’t have sufficient time to correct the students’ writing. Therefore, theauthentic assessment is difficult to be implemented. It is recommended that teachershave to be aware of these problems because teachers’ judgement on students’ writingcan become a crucial feedback for students to know how well they can do on writing.